51 Years of India-Bangladesh Bilateral Relations: Opportunities and Challenges - Md Akbor Ali (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2023)
Because of their distinct histories, India and Bangladesh have unique neighbourly relations. India and Bangladesh have completed 51 years of bilateral ties in 2022, beginning in December 1971 with India's recognition of the newly independent People's Republic of Bangladesh. India played a significant role in the formation of Bangladesh during a liberation conflict with Pakistan. There are many things that tie the two nations together, such as a shared history and legacy, linguistic and social ties, and a love of art that reflects the diversity of human expression in music, literature, and other forms. Bangladesh is a geopolitically and strategically important country in India's neighbourhood policy. Bangladesh is especially important to India because of its connectivity with the country's seven landlocked northern sister states. Bangladesh's foreign policy discourse is dominated by the words